Spatiotemporal evolution of investment-carbon emission coupling coordination in China’s electricity market - Zhang, Yuan; Zhang, Hongyuan; Hao, Feng (Frontiers in Energy Research, 2023)
Promoting the low-carbon development is the key to control CO2 emissions and achieve carbon neutrality in China, which requires the coordinated development between investment and carbon emissions in the electricity industry. Based on the panel data of electricity investment and carbon emissions in 30 provinces from 2000 to 2019, this paper systematically explains the coupling coordination mechanism between electricity investment and carbon emissions, and calculates the coupling coordination degree of each province through the coupling coordination model. Using GM (1,1) model to predict the coupling coordination development from 2020 to 2030. The study found that the development of China's electricity industry is in good condition. Although the coupling coordination degree of investment-carbon emission has entered the stage of barely and primary coordination in most provinces and regions, there have been certain fluctuations in recent years; There are spatial differences in regional coupling and coordinated development. Among them, the central region has a high level of coupling coordination, while the eastern and northeastern regions are relatively lagging behind; In the next 10 years, the coupling coordination degree between investment and carbon emissions in China's electricity industry will continue to grow. All regions can reach the primary coordination stage or above.